PENGARUH EFEKTIVITAS PENGENDALIAN INTERN, ASIMETRI INFORMASI DAN KESESUAIAN KOMPENSASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris Kantor Pusat Bank Perkreditan Rakyat Di Kota dan Kabupaten Malang) - Restu Putri Pamungkas; Istutik Istutik (Politeknik Negeri Malang, 2019)
The research aims to examine the effect of the effectiveness of internal control on trends in accounting fraud, examine the effect of information asymmetry on trends in accounting fraud, examine the effect of compensation appropriateness on accounting fraud trends. Qualitative research was carried out through in-depth surveys and interviews with the management of Islamic banks in Malang, customers, and academics about the need for an internal control system that is in accordance with the characteristics of Islamic banks. The development of an internal control system using the COSO (Committee of Sponsoring Organizations of The Treadway Commissions) framework was adopted and adapted to the characteristics of Islamic banks. The results of the study offer a model of an Islamic bank's internal control system through five components of the COSO, namely (1) the control environment, (2) risk assessment, (3) control activities, (4) information and communication, and (5) monitoring that will benefit banks sharia to achieve strategic and operational goals, accuracy of financial reporting, and compliance with applicable policies and laws. Thus it will be able to help eliminate risks so that the performance of profit-sharing based financing can also be improved